Entrepreneurial Characteristics and Sustainable Business: The Mediating Role of Perceived Ease of Use - Anna Widiastuti; Sisno Riyoko; Rias Untian Hanun; Cindi Ferdiani (Journal of Management and Entrepreneurship Research, 2026)
Objective: This study aims to examine how entrepreneurial characteristics and business experience influence business sustainability, with the perception of ease of use acting as a mediating variable in the context of financial technology adoption. Research Design & Methods: The study used a quantitative approach, targeting a population of MSMEs in potential sectors in Jepara Regency. A purposive sampling technique selected 190 MSMEs, including those using fintech services. Structural equation modelling (SEM-PLS) is used to analyse results by using partial least squares (PLS) to test both direct and indirect relationships between variables. Findings: The analysis results show that both entrepreneurial characteristics and business experience have a positive and significant direct effect on sustainable business practices. In a roundabout way, the perception of ease of use was found to mediate the effect of business experience on sustainable business practices, but this wasn’t the case for the entrepreneurial characteristics variable. Implications & Recommendations: The implications of the results of this study emphasize the importance of the ease of use of fintech services for MSMEs for business development. Contribution & Value Added: This study contributes to the development of the Technology Acceptance Model (TAM) by integrating entrepreneurial characteristics, business experience, and perceived ease of use to explain MSME sustainability through fintech adoption. The findings highlight that perceived ease of use strengthens the effect of business experience on sustainability, while entrepreneurial characteristics have a direct influence on sustainable business. These results provide practical insights for improving fintech services and digital literacy among MSMEs.